Pelaksanaan Perjanjian Kerjasama Bumdes Kelapa Sawit Dengan Pihak Kedua Di Desa Jelutih Kecamatan Batin XXIV - HS, Asmida; Naili Hidayah, Lili (Universitas Jambi, Fakultas Hukum, 2023)
This study aims to determine the position, authority, and responsibility of the parties in the memorandum of cooperation agreement. This study uses empirical juridical research methods. Based on these objectives, the formulation of the problem is obtained, namely how are the positions and authorities, and what are the responsibilities of the parties in the memorandum of agreement on cooperation between Palm Oil BUMDes and Second Parties in Jelutih Village, Batin District XXIV?. The research is expected to be useful for developing knowledge and insight in practicing scientific thinking skills in making scientific papers, and can be input for Palm Oil BUMDes with Second Parties in Jelutih Village, Batin District XXIV. From the results of the study, it is known that 1) The position and authority of the parties in the memorandum of agreement of cooperation are BUMDes Jelutih as the first party, namely as the provider of business funds (capital), while the Head of the Oil Palm Nursery Unit (second party) as the recipient of the power of attorney to carry out seed sales activities dominant palm oil. 2) The responsibility of the parties in the memorandum of understanding of cooperation is that the first party provides business funds and divides the business results in a 60:40 pattern, namely 60% for the first party and 40% for the second party, while the second party's responsibility is to carry out the work until all the seeds are planted. sold, control all the work in the field in the sale of oil palm seeds, and be responsible. Abstrak Penelitian ini bertujuan untuk mengetahui kedudukan, kewenangan, dan tanggung jawab para pihak dalam nota kesepakatan kerja sama. Penelitian ini menggunakan metode penelitian yuridis empiris. Berdasarkan tujuan tersebut diperoleh rumusan masalah yaitu bagaimana kedudukan dan kewenangan, dan bagaimana tanggung jawab para pihak dalam nota kesepakatan kerjasama BUMDes Kelapa Sawit dengan Pihak Kedua di Desa Jelutih Kecamatan Batin XXIV?. Penelitian diharapkan dapat bermanfaat untuk mengembangkan pengetahuan dan wawasan dalam melatih kemampuan berpikir ilmiah dalam pembuatan karya ilmiah, dan dapat menjadi masukan bagi BUMDes Kelapa Sawit dengan Pihak Kedua di Desa Jelutih Kecamatan Batin XXIV. Dari hasil penelitian, diketahui bahwa 1) Kedudukan dan kewenangan para pihak dalam nota kesepakatan kerja sama yaitu BUMDes Jelutih sebagai pihak pertama yaitu sebagai pemberi dana (modal) usaha, sedangkan Kepala Unit Pembibitan Sawit (pihak kedua) selaku penerima kuasa untuk melaksanakan kegiatan penjualan bibit sawit yang sangat mendominasi. 2) Tanggung jawab para pihak dalam nota kesepakatan kerja sama yaitu pihak pertama memberikan dana usaha dan membagi hasil usaha dengan pola 60:40 yaitu 60% untuk pihak pertama dan 40% untuk pihak kedua, sedangkan tanggung jawab pihak kedua adalah melaksanakan pekerjaan sampai semua bibit terjual, mengontrol semua pekerjaan di lapangan dalam penjualan bibit sawit, dan bertanggung jawab. Â